The Effectiveness of Stem Cell Therapy Compared to Conventional Therapy on Improving Pancreatic Beta Cell Function in Type 2 Diabetes Patients: A Systematic Review - Maulana Setiawan; Made Ratan Saraswati; Agus Eka Darwinata (Pattimura University, 2026)
More than 800 million people worldwide experience type 2 diabetes mellitus (T2DM), characterized by progressive pancreatic β-cell deterioration inadequately addressed by conventional treatments. This review assesses stem cell-based interventions versus standard therapy for β-cell functional restoration. Systematic review aims to comprehensively evaluate and compare the effectiveness of stem cell therapy versus conventional therapy in improving pancreatic β-cell function in type 2 diabetes patients. Systematic searches of PubMed, Cochrane Library, Web of Science, and Scopus from January 2015 to October 2025 retrieved 125 records. After duplicate removal and screening, 17 studies met the general inclusion criteria, of which six randomized controlled trials (RCTs) involving 339 participants were eligible for analysis. Primary outcomes were C-peptide concentrations, HOMA-β, HbA1c, insulin requirements, and safety parameters. The results showed that stem cell interventions consistently elevated fasting C-peptide levels to 1.9±1.0 ng/mL (versus 0.7±0.4 ng/mL in controls). Mean HbA1c reductions reached 0.67% (intervention 7.52±1.07% versus placebo 8.19±1.02%). Insulin dosage requirements decreased markedly, with reductions approaching 46.7%. Safety assessment remained limited due to incomplete adverse event documentation across included studies. Interpretation is further constrained by small trial sizes (23–91 participants) and protocol heterogeneity across cell sources, administration routes, and follow-up durations. Stem cell-based therapies demonstrate encouraging potential for enhancing pancreatic β-cell function in T2DM patients. Insufficient long-term follow-up data and inadequate safety surveillance preclude definitive clinical recommendations, supporting their application exclusively within structured clinical trial settings.